2019
DOI: 10.3390/nu12010096
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lycopene, [6]-Gingerol, and Silymarin on the Apoptosis on U-118MG Glioblastoma Cells In Vitro Model

Abstract: Background: Lycopene, gingerol, and silymarin have a potential anticancer activity in many types of neoplasms. Healthy lifestyle and proper diet are associated with a reduced risk of cancer and other diseases. Increasingly, clinical research focuses on the mechanisms of action of natural compounds and their impact on the development of cancer. The aim of the present study was to determine the effect of lycopene, gingerol, and silymarin on apoptosis, mitochondrial potential and caspase-3/7 activity in the U118-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Induced apoptosis [367][368][369][370]. Reduced cell viability and proliferation [368,370]. Silymarin nanoemulsion + cold atmospheric plasma reduced intracellular ATP levels and down-regulate transcriptional and survival pathways [371].…”
Section: Silymarinmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced apoptosis [367][368][369][370]. Reduced cell viability and proliferation [368,370]. Silymarin nanoemulsion + cold atmospheric plasma reduced intracellular ATP levels and down-regulate transcriptional and survival pathways [371].…”
Section: Silymarinmentioning
confidence: 99%
“…More recently, in a Burkkett's lymphoma model, silymarin induced apoptosis and caused a reduction in toll-like receptor 8 (TLR8) mRNA expression, implicating toll-like receptors in silymarin's anticancer activity [367]. Silymarin further decreased cell viability, increased apoptosis, and changed the mitochondrial membrane potential in glioblastoma cells [368]. Silymarin reduced cell viability and diminished migration of stomach cancer cells through the induction of apoptosis, inhibition of p-ERK and activation of p-p38 and p-JNK.…”
Section: Silymarinmentioning
confidence: 99%
“…16,26 6-Gingerol was reported to induce cell cycle arrest and exert antiinvasive and apoptosis promoting effects through acting on multiple signaling pathways in different types of cancer cell lines. [27][28][29] This seems to be at least partially connected to the antioxidant-prooxidant properties of 6-gingerol. This compound was reported to induce reactive oxygen species (ROS) generation leading to DNA damage in cancer cells.…”
Section: Anticancer Analoguesmentioning
confidence: 99%
“…Induction of apoptosis is one of the main strategies used in cancer treatment [ 37 , 38 ], including brain tumors [ 39 , 40 ]. Annexin V is one of the methods which is used to detect the cell apoptosis in the basis of live, early apoptotic, late apoptotic, and dead cell percentages according to asymmetry in the distribution of cell membrane phospholipids and the intracellularization of 7-AAD due to the cell membrane disruption [ 41 ]. Here, we investigated the effect of CP on apoptotic states of U87 and T98 cell lines and revealed that CP treatment induced mainly late apoptosis, evidence of the cell membrane rupture.…”
Section: Discussionmentioning
confidence: 99%